Bare laser‐synthesized Au‐based nanoparticles as nondisturbing surface‐enhanced Raman scattering probes for bacteria identification. Issue 7 (10th April 2018) - Kögler, Martin; Ryabchikov, Yury V.; Uusitalo, Sanna; Popov, Alexey; Popov, Anton; Tselikov, Gleb; Välimaa, Anna‐Liisa; Al‐Kattan, Ahmed; Hiltunen, Jussi; Laitinen, Riitta; Neubauer, Peter; Meglinski, Igor; et al.
Abstract : Methods of femtosecond laser ablation are used to fabricate bare Au‐based nanoparticles (NPs), which are then added to solutions of bacterial cultures and tested as surface‐enhanced Raman scattering (SERS) probes for bacteria identification. Profiting from NP‐induced enhancement of local electric fields, we demonstrate successful identification of 2 bacteria ( Listeria innocua and Escherichia coli ). The obtained results promise less disturbing studies of biological systems based on exceptional purity and good biocompatibility of laser‐synthesized nanomaterials. Abstract : The ability of noble metal‐based nanoparticles (NPs) (Au, Ag) to drastically enhance Raman scattering from molecules placed near metal surface, termed as surface‐enhanced Raman scattering (SERS), is widely used for identification of trace amounts of biological materials in biomedical, food safety and security applications. However, conventional NPs synthesized by colloidal chemistry are typically contaminated by nonbiocompatible by‐products (surfactants, anions), which can have negative impacts on many live objects under examination (cells, bacteria) and thus decrease the precision of bioidentification. In this article, we explore novel ultrapure laser‐synthesized Au‐based nanomaterials, including Au NPs and AuSi hybrid nanostructures, as mobile SERS probes in tasks of bacteria detection. We show that these Au‐based nanomaterials can efficiently enhance Raman signals from model R6G molecules, while the enhancement factor depends on the content of Au in NP composition. Profiting from the observed enhancement and purity of laser‐synthesized nanomaterials, we demonstrate successful identification of 2 types of bacteria ( Listeria innocua and Escherichia coli ). The obtained results promise less disturbing studies of biological systems based on good biocompatibility of contamination‐free laser‐synthesized nanomaterials.